Essentials of inorganic materials synthesis - Rao, C. N. R. (Chintamani Nagesa Ramachandra) 1934-; Biswas, Kanishka (Hoboken, New Jersey John Wiley & Sons, Ltd., 2014)
This compact handbook describes all the important methods of synthesis employed today for synthesizing inorganic materials.

Some features:

■ Focuses on modern inorganic materials with applications in nanotechnology, energy materials, and sustainability.
■ Synthesis is a crucial component of materials science and technology; this book provides a simple introduction as well as an updated description of methods.
■ Written in a very simple style, providing references to the literature to get details of the methods of preparation when required.
Includes bibliographical references and index.
Keywords: Inorganic compounds -- Synthesis